Forgiveness Analysis of Domestic Violence Victims in Aceh - Putri Fakhrina Sari; Afdal Afdal (Universitas Negeri Padang, 2019)
Forgiveness in this study is an apology from victims of domestic violence to perpetrators of domestic violence. The number of cases of domestic violence that occur is increasing from year to year, as victims of domestic violence choose to maintain their household, even though the victim is undergoing a household that experiences violence. Many ways are used by victims in maintaining their household, one of them is by giving forgiveness to perpetrators of domestic violence. This study aims to analyze how forgiveness of victims of domestic violence in Aceh province. The method used is the quantitative approach and the type of comparative descriptive research. The population in this study was the wife who was a victim of domestic violence in the city of Banda Aceh by taking a sample using a purposive sampling technique, the sample in this study was 31 victims of domestic violence. This study uses a self-composed instrument namely Forgiveness Scale for Domestic Violence (FosDiV) developed from the TRIM-18 questionnaire using a Likert scale model. Data analysis techniques in this study used quantitative descriptive. The results of this study indicate that overall forgiveness of victims of domestic violence in Aceh is in the medium category, which means they assume that giving forgivenees to perpetrators of domestic violence is a natural thing to do as a wife. In Aceh culture, a wife who is obedient and obedient to her husband is very important, wives feel happy when they are called by the term